The Effect Of Delay Time And Storage Temperature On The Results Of Urine Leukocyte Examination In Patients Of Urinary Tract Infection (UTI): Pengaruh Lama Waktu Penundaan Dan Suhu Penyimpanan Terhadap Hasil Pemeriksaan Leukosit Urine Pada Pasien Infeksi Saluran Kemih (ISK) - Krisdianti, Rika; Puspitasari, Puspitasari; Aliviameita, Andika (Medicra (Journal of Medical Laboratory Science/Technology), 2023)
Urinary Tract Infection (UTI) is a condition where there are microorganisms that multiply in the urinary tract causing inflammation and bacteriuria. The delay in the examination results in an error in diagnosis, the examination must be carried out >1 hour and a maximum of 2 hours after the voiding process at a temperature of 20-25℃ and the delay can be done a maximum of 4 hours at a temperature of 2-8℃. The study was conducted in June 2022. The study was conducted at SMK Muhammadiyah 1 Pandaan. UTI sampling at Sahabat Hospital in Suwayuwo Sukorejo. The purpose of this study was to determine the effect of delay time and storage temperature on the results of urine leukocyte examination in UTI patients. This study used an experimental method using 35 urine samples. The statistical test used the Two Way Anova test with a 95% confidence level and the inaccuracy limit of (α) = 0.05. Based on the results of the Two Way Anova test between storage temperature and delay in urine leukocytes, a significance value of 0.981 (p>0.05), it can be concluded that Ha is rejected and Ho is accepted, meaning that there is no interaction effect between the length of time delay and storage temperature on leukocyte results. urine in UTI patients.